Efektivitas Program Zakat dalam Pemberdayaan UMKM di Kecamatan Pasir Penyu, Kabupaten Indragiri Hulu - Yulia Febriyati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effectiveness of the zakat program in empowering Micro, Small, and Medium Enterprises (MSMEs) in Pasir Penyu District, Indragiri Hulu Regency. This study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Research informants consist of MSMEs who receive productive zakat and zakat managers. The results of the study indicate that the productive zakat program has a positive impact on MSME empowerment, especially in increasing business capital, business sustainability, and income stability of mustahik. In addition, the zakat program also encourages increased skills and motivation of MSMEs in managing their businesses. However, the effectiveness of the program still faces various obstacles, such as limited zakat funds, suboptimal business mentoring, and limited managerial capabilities and market access of MSMEs. The conclusion of this study shows that the productive zakat program in Pasir Penyu District, Indragiri Hulu Regency is quite effective in empowering MSMEs, but requires strengthening in terms of mentoring, program management, and business capacity development so that its impact is more optimal and sustainable.